Impact of oral anticoagulants on 30-day readmission: a study from a single academic centre. Issue 1 (2nd October 2018) - Bhattarai, Mukul; Hudali, Tamer; Robinson, Robert; Al-Akchar, Mohammad; Vogler, Carrie; Chami, Youssef
Abstract : Researchers are extensively searching for modifiable risk factors including high-risk medications such as anticoagulation to avoid rehospitalisation. The influence of oral anticoagulant therapy on hospital readmission is not known. We investigated the impact of warfarin and direct oral anticoagulants (DOACs) on all cause 30-day hospital readmission retrospectively in an academic centre. We study the eligible cohort of 1781 discharges over 2-year period. Data on age, gender, diagnoses, 30-day hospital readmission, discharge medications and variables in the HOSPITAL score (Haemoglobin level at discharge, Oncology at discharge, Sodium level at discharge, Procedure during hospitalisation, Index admission, number of hospital Admissions, Length of stay) and LACE index (Length of stay, Acute/emergent admission, Charlson comorbidity index score, Emergency department visits in previous 6 months), which have higher predictability for readmission were extracted and matched for analysis. Warfarin was the most common anticoagulant prescribed at discharge (273 patients) with a readmission rate of 20% (p<0.01). DOACs were used by 94 patients at discharge with a readmission rate of 4% (p=0.219). Multivariate logistic regression showed an increased risk of readmission with warfarin therapy (OR 1.36, p=0.045). Logistic regression did not show DOACs to be a risk factor for hospital readmission. Our data suggests that warfarin therapy is a risk factor for all-cause 30-day hospital readmission. DOAC therapy is not found to be associated with a higher risk of hospital readmission. Warfarin anticoagulation may be an important target for interventions to reduce hospital readmissions.